"Prophetic vision, vivid imagination": The 1927 Mississippi River flood. Issue 12 (28th December 2015) - Smith, James A.; Baeck, Mary Lynn
Abstract: The 1927 flood in the Lower Mississippi River was the most destructive flood in American history, inundating more than 70, 000 km 2 of land, resulting in approximately 500 fatalities and leaving more than 700, 000 people homeless. Despite the prominence of the 1927 flood, details on the flood, and the storms that produced the flood, are sparse. We examine the hydrometeorology and hydroclimatology of the 1927 flood in the Lower Mississippi River through downscaling simulations of the storms that were responsible for catastrophic flooding and through empirical analyses of rainfall and streamflow records. We use Twentieth Century Reanalysis fields as boundary conditions and initial conditions for downscaling simulations using the Weather Research and Forecasting (WRF) model. We place the hydrometeorological analyses of the 1927 storms in a hydroclimatological context through analyses of the Twentieth Century Reanalysis fields. Analyses are designed to assess the physical processes that control the upper tail of flooding in the Lower Mississippi River. We compare the 1927 flood in the Lower Mississippi River to floods in 1937 and 2011 that represent the most extreme flooding in the Lower Mississippi River. Key Points: The 1927 flood in the Lower Mississippi River was the most damaging flood in U.S. history Rainfall over the Lower Mississippi River is related to water vapor flux from Gulf of Mexico WRF model results illustrate utility of simulations using Twentieth Century Reanalysis for floods